Maternal and neonatal outcomes of antenatal anemia in a Scottish population: a retrospective cohort study. (1st March 2016) - Rukuni, Ruramayi; Bhattacharya, Sohinee; Murphy, Michael F.; Roberts, David; Stanworth, Simon J.; Knight, Marian
Abstract: Introduction: Antenatal anemia is a major public health problem in the UK, yet there is limited high quality evidence for associated poor clinical outcomes. The objectives of this study were to estimate the incidence and clinical outcomes of antenatal anemia in a Scottish population. Material and methods: A retrospective cohort study of 80 422 singleton pregnancies was conducted using data from the Aberdeen Maternal and Neonatal Databank between 1995 and 2012. Antenatal anemia was defined as haemoglobin ≤10 g/dl during pregnancy. Incidence was calculated with 95% confidence intervals and compared over time using a chi‐squared test for trend. Multivariable logistic regression was used to adjust for confounding variables. Results are presented as adjusted odds ratios with 95% confidence interval. Results: The overall incidence of antenatal anemia was 9.3 cases/100 singleton pregnancies (95% confidence interval 9.1–9.5), decreasing from 16.9/100 to 4.1/100 singleton pregnancies between 1995 and 2012 ( p < 0.001). Maternal anemia was associated with antepartum hemorrhage (adjusted odds ratio 1.26, 95% confidence interval 1.17–1.36), postpartum infection (adjusted odds ratio 1.89, 95% confidence interval 1.39–2.57), transfusion (adjusted odds ratio 1.87, 95% confidence interval 1.65–2.13) and stillbirth (adjusted odds ratio 1.42, 95% confidence interval 1.04–1.94), reduced odds of postpartum hemorrhage (adjusted odds ratio 0.92, 95% confidence interval 0.86–0.98) and low birthweight (adjusted odds ratio 0.77, 95% confidence interval 0.69–0.86). No other outcomes were statistically significant. Conclusions: This study shows the incidence of antenatal anemia is decreasing steadily within this Scottish population. However, given that anemia is a readily correctable risk factor for major causes of morbidity and mortality in the UK, further work is required to investigate appropriate preventive measures.